Introducing the ancient Greeks from bronze age seafarers to navigators of the western mind - Hall, Edith 1959- (W. W. Norton and Company, 2014)
Examines the ancient Greeks, from the rise of the Mycenaean kingdoms to the victory of Christianity over paganism, focusing on the qualities that characterized the widely diffused Mediterranean people over the long course of their history.